Design optimization of connecting rod for internal combustion engine - Mohd Shamil, Shaari (2010)
This project describes the study of topology optimization for connecting rod of internal combustion engine. The objectives of this study are to develop structural modelling, finite element analysis and the optimization of the connecting rod for robust design using topology optimization technique. The structure of connecting rod was modelled using SOLIDWORKS software. Finite element modelling and analysis were performed using MSC.PATRAN and MSC.NASTRAN software. Linear static analysis was carried out to obtain the stress/strain state results. The mesh convergence analysis was performed to select the best mesh for the analysis. The topology optimization technique is used to reduce the weight of the connecting rod. From the FEA analysis results, TET10 predicted higher maximum stress than TET4 and maximum principal stress captured the maximum stress. From the topology optimization, the crank end was suggested to be redesign. The optimized connecting rod is 11.7% lighter and predicted lower maximum stress compare to initial design. For future research, the optimization should cover on material optimization to increase the strength of the connecting rod